Isolated glycogen storage disease of the heart - S. M. Komissarova; N. M. Rineiskaya; N. N. Chakova; S. S. Niyazova; L. I. Plashchinskaya (Российский кардиологический журнал)
Isolated glycogen storage disease of the heart (PRKAG2 syndrome) is a form of glycogenosis, which is characterized by left ventricular hypertrophy, similar to the phenotype of hypertrophic cardiomyopathy, associated with pre-excitation of the ventricles and conduction disorders. The disease is caused by mutations in the gene PRKAG2 encoding for the 5’Adenosine Monophosphate-Activated Protein Kinase (AMPK), specifically for its y2 regulatory subunit, inheritance — autosomal dominant. A review of the literature data and clinical observation of two patients from the same family with the mutation c905C>A (p.Arg302Gln) in the PRKAG2 gene associated with WPW syndrome and early development of conduction disorders requiring implantation of a pacemaker are presented. The issues of diagnosis and treatment strategy of the disease were discussed.